Seed Physiology of some Pulses and Cereals under the Influence of Acacia arabica Gum - Ashok M. Chavan, K.V. Badar and (Recent Research in Science and Technology, 2011)
Present paper deals with the study of impact of Acacia arabica gum solution on seed germination, root and shoot length of some pulses like cowpea, gram and some cereals like wheat and maize. It was found that Acacia arabica gum induces the seed germination, root and shoot length.